Advertisements
Advertisements
Question
Find the general solution of the following differential equation :
`(1+y^2)+(x-e^(tan^(-1)y))dy/dx= 0`
Solution
Given:
`(1+y^2)+(x-e^(tan^(-1)y))dy/dx= 0`
Let tan−1y=t
⇒y=tant
`=>dy/dx=sec^2tdt/dx`
Therefore, the equation becomes
(1+tan2t)+(x−et)sec2t `dt/dx=0`
`=>sec^2t+(x-e^t)(sec^2t)dt/dx=0`
`=>1+(x-e^t)dt/dx=0`
`=>(x-e^t)dt/dx=-1`
`=>x-e^t=dx/dt`
`=>dx/dt+1.x=e^t`
If =e∫1.dt
= et
`:. e^t.(dx/dt+1.x)=e^t.e^t`
`=>d/dt(xe^t)=e^(2t)`
Integrating both the sides, we get
`xe^t=inte^(2t)dt`
`=>xe^t=1/2e^(2t)+C " ....(1)"`
Substituting the value of t in (1), we get
`xe^(tan^(1))y=1/2e^(2tan^(-1)y)+C_1`
`=>e^2tan^(-1y)=2xe^(tan^1y)+C`
It is the required general solution.
APPEARS IN
RELATED QUESTIONS
The differential equation of `y=c/x+c^2` is :
(a)`x^4(dy/dx)^2-xdy/dx=y`
(b)`(d^2y)/dx^2+xdy/dx+y=0`
(c)`x^3(dy/dx)^2+xdy/dx=y`
(d)`(d^2y)/dx^2+dy/dx-y=0`
The solution of the differential equation dy/dx = sec x – y tan x is:
(A) y sec x = tan x + c
(B) y sec x + tan x = c
(C) sec x = y tan x + c
(D) sec x + y tan x = c
Verify that the given function (explicit or implicit) is a solution of the corresponding differential equation:
y = ex + 1 : y″ – y′ = 0
Verify that the given function (explicit or implicit) is a solution of the corresponding differential equation:
`y = sqrt(a^2 - x^2 ) x in (-a,a) : x + y dy/dx = 0(y != 0)`
The number of arbitrary constants in the particular solution of a differential equation of third order are ______.
The solution of the differential equation \[\frac{dy}{dx} = 1 + x + y^2 + x y^2 , y\left( 0 \right) = 0\] is
Solution of the differential equation \[\frac{dy}{dx} + \frac{y}{x}=\sin x\] is
The solution of x2 + y2 \[\frac{dy}{dx}\]= 4, is
Which of the following differential equations has y = x as one of its particular solution?
The general solution of the differential equation \[\frac{y dx - x dy}{y} = 0\], is
Find the particular solution of the differential equation `(1+y^2)+(x-e^(tan-1 )y)dy/dx=` given that y = 0 when x = 1.
x (e2y − 1) dy + (x2 − 1) ey dx = 0
\[\frac{dy}{dx} + 1 = e^{x + y}\]
\[\frac{dy}{dx} = \left( x + y \right)^2\]
cos (x + y) dy = dx
\[\frac{dy}{dx} - y \cot x = cosec\ x\]
`(2ax+x^2)(dy)/(dx)=a^2+2ax`
\[x\frac{dy}{dx} + x \cos^2 \left( \frac{y}{x} \right) = y\]
For the following differential equation, find the general solution:- \[\frac{dy}{dx} = \left( 1 + x^2 \right)\left( 1 + y^2 \right)\]
For the following differential equation, find the general solution:- `y log y dx − x dy = 0`
Solve: `2(y + 3) - xy "dy"/"dx"` = 0, given that y(1) = – 2.
Solve the differential equation (1 + y2) tan–1xdx + 2y(1 + x2)dy = 0.
The differential equation for y = Acos αx + Bsin αx, where A and B are arbitrary constants is ______.
The number of solutions of `("d"y)/("d"x) = (y + 1)/(x - 1)` when y (1) = 2 is ______.
The solution of `("d"y)/("d"x) + y = "e"^-x`, y(0) = 0 is ______.
The solution of the differential equation cosx siny dx + sinx cosy dy = 0 is ______.
Solution of the differential equation `("d"y)/("d"x) + y/x` = sec x is ______.
The solution of `("d"y)/("d"x) = (y/x)^(1/3)` is `y^(2/3) - x^(2/3)` = c.
Find a particular solution, satisfying the condition `(dy)/(dx) = y tan x ; y = 1` when `x = 0`